2015
DOI: 10.5433/1679-0359.2015v36n5p385
|View full text |Cite
|
Sign up to set email alerts
|

Acúmulo de óleo em sementes de soja cultivadas in vitro e in vivo

Abstract: <p>A semente de soja apresenta, cerca de 20% da sua massa seca em óleo e 40% em proteína. Esse teor de óleo pode sofrer influência perante as condições ambientais durante o enchimento das sementes, produzindo modificações na sua composição bioquímica. Em condições de cultivo <em>in vivo </em>é difícil controlar esse fator. Nesse sentido, o cultivo <em>in vitro </em>vem auxiliar a pesquisa, pois a semente fica isolada da planta mãe em ambiente controlado. O objetivo deste trabalho … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…According to Li et al (2019), although the oil content is genetically ruled, it is also strongly influenced by environmental factors. These results are in line with those found by Albrecht et al (2008), Bruno et al (2015) and Faria et al (2018), who also observed an increased oil content in grains of plants grown under high temperatures and/or with less water availability in the grain-filling stage. However, Rotundo & Westgate (2009) observed an overall negative impact of the water deficit on the oil content of soybean seeds in general.…”
Section: Resultssupporting
confidence: 92%
“…According to Li et al (2019), although the oil content is genetically ruled, it is also strongly influenced by environmental factors. These results are in line with those found by Albrecht et al (2008), Bruno et al (2015) and Faria et al (2018), who also observed an increased oil content in grains of plants grown under high temperatures and/or with less water availability in the grain-filling stage. However, Rotundo & Westgate (2009) observed an overall negative impact of the water deficit on the oil content of soybean seeds in general.…”
Section: Resultssupporting
confidence: 92%